2011
DOI: 10.1590/s0034-71672011000500020
|View full text |Cite
|
Sign up to set email alerts
|

Auditoria em enfermagem: revisão sistemática da literatura

Abstract: RESUMOEste estudo teve como objetivo analisar a produção científi ca acerca da auditoria em enfermagem publicada em artigos nacionais entre 1998 e 2008. Realizou-se uma revisão sistemática da literatura, com os artigos sendo pesquisados nas bases de dados LILACS e SciELO, a partir dos descritores auditoria, auditoria de enfermagem, qualidade da assistência à saúde e supervisão de enfermagem. A amostra constituiu-se de dez trabalhos. As publicações analisadas descrevem as principais distorções e não conformidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
31

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 10 publications
0
11
0
31
Order By: Relevance
“…It should be emphasized that it is a legal obligation of the nursing professional to correctly record their activities, and the institution should establish norms and routines that guide both the correct record and the correction of an inadequate record. It was verified the need to implement educational measures to obtain quality in the registries and care provided, with the awareness of the professionals to the reliable registry which favors the continuity of patient care and safety [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be emphasized that it is a legal obligation of the nursing professional to correctly record their activities, and the institution should establish norms and routines that guide both the correct record and the correction of an inadequate record. It was verified the need to implement educational measures to obtain quality in the registries and care provided, with the awareness of the professionals to the reliable registry which favors the continuity of patient care and safety [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…It is a tool that contributes to the improvement of health services and practices, mainly in diverse and complex structures such as the SUS system. At the same time, it should be emphasized that the quality of the nursing record contributes positively to multidisciplinary communication, but often the shortage of nursing staff in hospitals makes it difficult to record information [13,17,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta reflexão é capaz de gerar novas idéias e possibilidades para as atividades diárias de cuidado. A participação do enfermeiro como educador, no que tange a auditoria, confere empoderamento a este profissional no ambiente hospitalar 19 . Realizar educação permanente é fundamental, porém também se faz necessário que o enfermeiro tenha uma conduta de adequada frente suas atividades para que seja visto como exemplo pela equipe, afinal a função do enfermeiro não se resume apenas em supervisionar a equipe 20 .…”
Section: Papel Do Enfermeiro Em Auditoria Hospitalarunclassified
“…It is observed that the audit has become an essential practice in the transformation of work processes that has been happening in hospitals and health plan operators, aiming at the restructuring to guarantee the quality of care and at the same time maintain a competitive position in the labor market. 12,13 In this way, the nurse auditor, when playing his role within the ethical and legal principles of the profession, becomes fundamental in the management of health services, since it can guarantee quality of care, reduce costs, eliminate fraud, through the effectiveness of the quality of service delivery. It is understood that the graduate programs contribute to the qualification of the professionals with the accomplishment of researches that innovate and provoke the expansion of the knowledge.…”
Section: Introductionmentioning
confidence: 99%